The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1080/20008198.2022.2083375
|View full text |Cite
|
Sign up to set email alerts
|

Skin conductance response to trauma interview as a candidate biomarker of trauma and related psychopathology in youth resettled as refugees

Abstract: Background: Posttraumatic stress symptoms (PTSS) include a constellation of physical and emotional profiles that youth exposed to trauma may experience. An estimated 20% of youth are exposed to trauma, and in refugee populations, up to 54% experience posttraumatic stress. Given the physical and mental health consequences associated with trauma exposure and subsequent psychopathology, identifying biomarkers of symptom severity is a top research priority. Objective: Previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 79 publications
1
7
0
Order By: Relevance
“…Our data also point toward greater threat reactivity in youth with higher trauma exposure and corroborate findings using other measures of threat reactivity in youth (Grasser et al., 2022). FPS to both threat and safety cues was positively correlated with trauma exposure, and discrimination was better in the higher trauma group, indicative of greater threat reactivity.…”
Section: Discussionsupporting
confidence: 90%
“…Our data also point toward greater threat reactivity in youth with higher trauma exposure and corroborate findings using other measures of threat reactivity in youth (Grasser et al., 2022). FPS to both threat and safety cues was positively correlated with trauma exposure, and discrimination was better in the higher trauma group, indicative of greater threat reactivity.…”
Section: Discussionsupporting
confidence: 90%
“…Some psychophysical markers in patients with PTSD were also investigated. One promising candidate is skin conductance (SC), which was found to be increased in patients with PTSD [ 213 , 214 ]. Although resting blood pressure was found to be elevated in PTSD patients [ 186 , 187 ], further studies are needed to assess its feasibility as a biophysical marker.…”
Section: Ptsd Biomarkersmentioning
confidence: 99%
“…Indeed, similar to the NIMH's Research Domain Criteria (RDoC) initiative (Cuthbert & Kozak, 2013), the Expressive Therapies Continuum considers cross‐cutting features that are present across various techniques (e.g., movement, social connection) and may have overlapping mechanistic underpinnings. Techniques leaning toward the kinesthetic/sensory end of the continuum may be more strongly rooted in moving the body in aerobic and rhythmic ways to quell systemic inflammation (Cooper et al, 2004; Grasser, 2022; Izadpanah et al, 2012), stimulate endocannabinoid signaling (Desai et al, 2022), regulate the balance between sympathetic and parasympathetic nervous system activity, and use movement as a form of nonverbal emotional expression. Interventions that engage perceptual/affective experiences may foster the use of creative media for personal expression and help strengthen emotion regulation.…”
Section: Mind–body Interventions: the “What” “How” And “Why”mentioning
confidence: 99%
“…The STARC Lab has shown that dance/movement and art therapy programs can be scaled up for implementation through virtual learning platforms, to reach a wider group of school‐age children across virtual and in‐person settings (Grasser & Javanbakht, 2021), and through community groups to facilitate neighborhood‐level interventions. Indeed, the initial success of and evidence from these programs has led to partnership with and funding from the State of Michigan's Office of Global Michigan to bring creative arts and movement therapies to all five major resettlement sites across the state to serve New Americans from Syria, Afghanistan, Burma, the Democratic Republic of the Congo, Ukraine, and other nations (Feen‐Calligan et al, 2020; Grasser, 2022; Grasser et al, 2019; Grasser & Javanbakht, 2021). To date, over 600 New Americans and metro Detroiters have engaged in these programs (Grasser, 2022).…”
Section: Mind–body Interventions: the “What” “How” And “Why”mentioning
confidence: 99%
See 1 more Smart Citation